Assessing the impact of individual nutrition on biodiversity: A conceptual framework for the selection of indicators targeted at the out-of-home catering sector - Silvia Monetti (Elsevier, 2021)
Agriculture is an economic sector with massive impact on biodiversity and agrobiodiversity. Sustainable diets represent a critical policy leverage and a realistic opportunity to reduce the environmental impact of the agro-food sector while improving human health at the same time. Eating out is an increasingly common habit for many consumers and, by offering sustainable dishes, catering companies can play a central role. To do this, they need to understand and correctly assess the sustainability of their food portfolio, but assessment tools are not well established yet. The NAHGAST project, of which this study was part, developed and tested a sustainability assessment tool for catering companies based on concrete targets defined per meal. This study addresses the lack of methods to evaluate the impact of food on biodiversity, with a particular focus on agrobiodiversity. The work illustrates a context-specific application of an enhanced DPSIR model to structure information and select indicators, and proposes a transdisciplinary use of existing metrics. Further research is needed in order to define scientifically sound target values or sustainability ranges for each indicator per meal, in order to calculate them. Strengths and limits of the study are discussed.